ANALISIS STATUS ASAM ASCORBAT, NILAI LIMFOSIT DAN LAMA PENGEBOTAN PASIEN TB MDR DI RSUD SOEWONDO PATI - SIfa Altika; Irfana Tri Wijayanti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
TB MDR is an infection caused by mycobacterium tuberculosis that is resistant OATs. OAT resistance causes an increase in free radicals and a decrease in antioxidants, one type of antioxidant in the body is ascobat acid. The purpose of this study was to analyze the ascorbic acid status, lymphocyte value and duration of treatment for TB MDR patients by conducting tests to detect, measure and analyze ascorbic acid status, lymphocyte values, and length of treatment for TB MDR patients. This study uses a case control. The sample used total sampling with a ratio of 1: 1 between the case group and the control group. Samples were obtained based on the order in which the patients visited RSUD Soewondo Pati during the study period (consecutive sampling). The sample of this study was 20 case groups and 20 control groups. The results of this study based on the Mann Whitney test, it shows that there is a difference between the total ascorbic acid in the case group and the control group with a value of p = 0.027 <0.05. And there is a difference in lymphocyte values in the case group and the control group p = 0.000 <0.05. Based on these results the mean lymphocyte and ascorbic acid values of the control group were higher than the case group, although showing differences in lymphocyte values in the case and control groups showed that the mean of each group showed Vitamin C deficiency. Based on the results of the study, it is suggested to develop interventions giving Vitamin C to the perceived healing of TB MDR patients.